'Died from Debeeration': the Case of the First Belarusian Political Game. Issue 1 (2nd January 2023) - Serada, Alesha
Abstract: Early computer games of the 'Eastern bloc' have been studied as important artefacts of early digital media, but their significance is usually limited to the historical context. In this article, I present a case study of the first popular computer game made in Belarus, which political relevance has persisted through over two decades. In order to achieve multi-sided description and interpretation of the case, three methods are combined: semantic analysis of the game itself, a survey of its typical players, and comparison to similar cases in Czechoslovakia, Poland and Russia. The proposed explanation of the game's origins highlights the importance of 'shared commons', relics of socialism reused for a variety of purposes during the brief period of ideological liberalism. This allows situating this particular form of subversive media in the process of transition from socialism to capitalism in Eastern Europe – the process that has never been concluded in contemporary Belarus, contributing to the totalitarian situation of 2020–2021.